Polyphony of Voices and the Silent-Others: A Reflection of Anthropocentrism at the Gabriela Mistral School in Popayán, Colombia - Jaramillo-Echeverry, Luis Guillermo (2024)
This paper presents part of the findings from the research project Sense of Respect for Life: Between the Silent-Other and the School, conducted as part of a master’s degree in education at the University of Cauca, Colombia. We explore the way in which humans have positioned themselves as 'superior beings' in their relationship with animals, referred to as the Silent Others by San Martín (2016). The objective was to understand the sense of respect for life attributed to the Silent-Other by students and teachers in the field of Natural Sciences in the eighth grade at the Gabriela Mistral School in the city of Popayán. We followed the phenomenological method based on Lester Embree's (2003) Reflective Analysis proposal, which allowed us to achieve the three phenomenological reductions: natural, eidetic, and transcendental. The study revealed an anthropocentric perspective of the Silent-Others, perceiving them as beings with human-like feelings and upon whom the selfhood of humans is projected.